The prevalence of tick-borne encephalitis in the region of West Bohemia (Czech Republic) between 1960-2005 - Pazdiora, Petr; Benesová, Jindriska; Böhmová, Zdenka; Králíková, Jitka; Kubátová, Anna; Menclová, Irena; Morávková, Ivana; Průchová, Jitka; Prechová, Marie; Spácilová, Marika; Vodrázková, Zuzana; Struncová, Vera; et al. (Wiener medizinische Wochenschrift (1946), 2008)
Between 1960-2005, 1,621 cases of tick-borne encephalitis were confirmed by laboratory testing in the region of West Bohemia (now the regions of Pilsen and Karlovy Vary) which represents a rate of infection of 4.1 per 100,000 inhabitants per year. The highest infection rate was established in men aged 20-24 and women aged 45-54. Over the monitored years, there was a significant shift of the maximum infection rate into an older age group. Currently, it is the 45-64 age group which carries the highest rate of infection. Of the identified disease cases, 12 were lethal, which represents 0.7% of the total. Over the years, the risks of transmission in particular areas of the region have changed. The highest infection rate is currently in the district of Klatovy (21.7 per 100,000 inhabitants per year). Of the total number, only two cases were contracted outside the Czech Republic (Slovakia and Austria). In 4.8% cases, the patient's anamnesis showed data on the consumption of non-pasteurized milk. 3.0% of infections probably originated as a result of professional exposure. Over the years, the season of infection has extended. Presently, the transmission can occur anytime between March and November. According to official data, only 6.7% of the population in the Pilsen district has been vaccinated so far. The low percentage of vaccinated cases may, however, in no way influence the unfavorable epidemiological situation regarding tick-borne encephalitis.
Keywords: Young Adult; Cross-Sectional Studies; Male; Child, Preschool; mladý dospělý; Adolescent; Infant; Česká republika; Child; skleníkový efekt; Greenhouse Effect; dítě; Adult; Encephalitis Viruses, Tick-Borne; Aged; dospělí; mužské pohlaví; senioři; incidence; mladiství; Encephalitis, Tick-Borne; Czech Republic; Viral Vaccines; předškolní dítě; Animals; lidé; ženské pohlaví; roční období; Seasons; Humans; zvířata; klíšťová encefalitida; mléko; kojenec; průřezové studie; viry klíšťové encefalitidy; Female; lidé středního věku; Incidence; virové vakcíny; Milk; Middle Aged